The Development of Islamic Accounting Standards in Vietnam: Challenges and Opportunities for Harmonization - Cham Is Na Uy (PT. Hassan Group Publisher, 2025)
The development of Islamic accounting standards has gained global attention alongside the growth of Islamic economics, including in Vietnam, where Muslims represent a minority population. This study aims to analyze the challenges and opportunities in developing Islamic accounting standards in Vietnam and to examine the potential for harmonization with international frameworks such as AAOIFI. A qualitative method with a descriptive-analytical approach was employed, drawing on literature reviews, policy documents, and comparative studies of countries with more advanced Islamic accounting systems. The findings reveal that the main barriers involve regulatory gaps, institutional capacity, and human resource limitations, yet substantial opportunities exist through ASEAN regional integration, the expansion of the halal industry, and increasing cross-border investments. The study implies the need for policy reforms, institutional strengthening, and international cooperation to accelerate the adoption of Islamic accounting standards in Vietnam